1998
DOI: 10.1002/(sici)1097-0142(19980915)83:6<1128::aid-cncr11>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Desmoplastic and desmoplastic neurotropic melanoma

Abstract: BACKGROUND It has been suggested that desmoplastic melanoma (DM) and desmoplastic neurotropic melanoma (DNM) are associated with worse prognoses and higher local recurrence rates than other forms of melanoma. In the current study, a large series of patients with DM and DNM treated at a tertiary referral center was reviewed. METHODS For 190 patients with DM and 90 patients with DNM accrued over a 10‐year period, clinical features were recorded and all available histopathology was reviewed. The associations betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
108
2
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 264 publications
(117 citation statements)
references
References 22 publications
5
108
2
2
Order By: Relevance
“…1,6,11,13,15,17 Nodal metastasis rates for non-DM of comparable thickness (>3 mm) are >25 %, which is far greater than the rates reported for DM. 1,7,11,2329 Furthermore, Livestro et al 6 case-matched DM and non-DM patients by age, gender, and tumor thickness and showed that SLN metastasis rates were significantly lower for DM (8 %) compared with non-DM (33.8 %, p = .13). These results suggest that DM may behave in a biologically unique manner with a lower propensity for metastasizing to regional nodes.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…1,6,11,13,15,17 Nodal metastasis rates for non-DM of comparable thickness (>3 mm) are >25 %, which is far greater than the rates reported for DM. 1,7,11,2329 Furthermore, Livestro et al 6 case-matched DM and non-DM patients by age, gender, and tumor thickness and showed that SLN metastasis rates were significantly lower for DM (8 %) compared with non-DM (33.8 %, p = .13). These results suggest that DM may behave in a biologically unique manner with a lower propensity for metastasizing to regional nodes.…”
Section: Discussionmentioning
confidence: 77%
“…14 DM is usually found on the head and neck of older males and often presents as a thicker tumor compared with nondesmoplastic melanoma (non-DM). 1,47 Despite the greater thickness, some studies report lower rates of nodal metastases compared with non-DM, suggesting a potentially different biologic behavior. 6,8 Interestingly, activating BRAF V600E mutations, present in ∼50 % of non-DM, are lacking in DM, providing further evidence for a different biology.…”
mentioning
confidence: 99%
“…45 Histologically, it is characterized by pleomorphic dermal spindle cells with a marked fibrogenic (stromal) component and may exhibit perineural invasion, intraneural invasion and neural transformation. Clinically, DM presents as a subtle plaque, nodule or dermal thickening which is often (46-93%) amelanotic 46 in chronically sun exposed areas and may be occasionally associated with adjacent lentigo maligna.…”
Section: Introductionmentioning
confidence: 99%
“…It is more common in older patients (median age 61 years). 45 Given the nondescript histological and clinical findings, DM is often initially misdiagnosed. As such, patients often present late with locally advanced, thicker lesions (mean Breslow depth 6.5 mm) with malignant cells extending deeply into the reticular dermis and subcutaneous tissue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation